Outbreak of OXA-232-producing carbapenem-resistant Klebsiella pneumoniae ST15 in a Chinese teaching hospital: a molecular epidemiological study - Wu, Xiaoyan; Li, Xiangchen; Yu, Junjie; Shen, Mengli; Fan, Chenliang; Lu, Yewei; Gao, Junshun; Li, Xiaosi; Li, Hongsheng (Frontiers in Cellular and Infection Microbiology, 2023)
Background and Aims The incidence of OXA-232-producing carbapenem-resistant Klebsiella pneumoniae (CRKP) has been on the rise in China over the past five years, potentially leading to nosocomial epidemics. This study investigates the first outbreak of CRKP in the Second Affiliated Hospital of Jiaxing University. Methods Between February 2021 and March 2022, 21 clinical isolates of OXA-232-producing CRKP were recovered from 16 patients in the Second Affiliated Hospital of Jiaxing University. We conducted antimicrobial susceptibility tests, whole genome sequencing, and bioinformatics to determine the drug resistance profile of these clinical isolates. Results Whole-genome sequencing revealed that all 21 OXA-232-producing CRKP strains belonged to the sequence type 15 (ST15) and shared similar resistance, virulence genes, and plasmid types, suggesting clonal transmission between the environment and patients. Integrated genomic and epidemiological analysis traced the outbreak to two clonal transmission clusters, cluster 1 and cluster 2, including 14 and 2 patients. It was speculated that the CRKP transmission mainly occurred in the ICU, followed by brain surgery, neurosurgery, and rehabilitation department. Phylogenetic analysis indicated that the earliest outbreak might have started at least a year before the admission of the index patient, and these strains were closely related to those previously isolated from two major adjacent cities, Shanghai and Hangzhou. Comparative genomics showed that the IncFII-type and IncHI1B-type plasmids of cluster 2 had homologous recombination at the insertion sequence sites compared with the same type of plasmids in cluster 1, resulting in the insertion of 4 new drug resistance genes, including TEM-1, APH(6)-Id, APH(3’’)-Ib and sul2. Conclusions Our study observed the clonal spread of ST15 OXA-232-producing between patients and the hospital environment. The integration of genomic and epidemiological data offers valuable insights and facilitate the control of nosocomial transmission.